Neuroprotective abilities and cognitive enhancing effects of red jasmine rice extract in animal model of Alzheimer’s disease - Phachonpai, Wathita; Wattanathorn, Jintanaporn; Tong-Un, Terdthai (Health Science, Science and Technology Reviews, 2015)
The aim of the study is to evaluated the neuroprotective effect of the red jasmine rice extract and tested the beneficial effect on memory impairments induced the rat ethylcholine mustard azirinium ion (AF64A) injection model of Alzheimer’s disease. After that the male Wistar rats were supplemented with the red jasmine rice extract at doses of 250 and 500 mg/kg BW once daily continually for 2 weeks. Cognition was evaluated using the Morris water maze test. Both doses of extract supplementation significantly prevented changes of spatial memory of AF64A treated rats. The cognitive enhancement of the extract was found to be related to its ability to inhibit the degeneration of neurons in hippocampus. It is suggested that red jasmine rice extract may prevent the dementia of the Alzheimer type.